Peran Pendidikan Holistik dan Komprehensif dalam Membentuk Karakter Islami pada Peserta Didik - Alpin Maulana; Ayu Rahmawati; Dewi Nurhaliza; Abdul Azis (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
This study discusses the role of holistic and comprehensive education in shaping the Islamic character of students through an integrative approach that includes physical, intellectual, emotional, social, and spiritual aspects. This study aims to evaluate the extent to which a holistic educational approach can contribute to the formation of Islamic character rooted in the values ​​of Islamic teachings, while supporting the goals of Islamic Religious Education (PAI) in the context of formal education. The method used is descriptive qualitative research with a literature study approach, which involves analysis of various scientific sources, including journals, reference books, and relevant articles. The results of the study indicate that holistic and comprehensive education is able to shape the Islamic character of students comprehensively and contextually, in line with the principles of PAI. This study also emphasizes the importance of integrating character values ​​through the curriculum, learning methods, and the role of teachers and the environment as the main supporters of the success of Islamic character education. Thus, character education based on a holistic and comprehensive approach can be an effective model in responding to the moral and spiritual challenges of students in the modern era.